2021
DOI: 10.2196/19046
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Correlation Between Depression and Social Behavior on Smartphones Through Usage Metadata: Empirical Study

Abstract: Background As smartphone has been widely used, understanding how depression correlates with social behavior on smartphones can be beneficial for early diagnosis of depression. An enormous amount of research relied on self-report questionnaires, which is not objective. Only recently the increased availability of rich data about human behavior in digital space has provided new perspectives for the investigation of individual differences. Objective The obj… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 86 publications
(37 reference statements)
1
5
1
Order By: Relevance
“…In addition, we confirmed the potential discriminative validity of smartphone biomarkers observed among adults in a youth sample [ 51 ]. Although our results on the number of outgoing calls negatively correlating with internalizing symptoms are in line with previous studies in adults [ 13 , 15 , 18 ], differences in mobility patterns of youths with high anxiety symptoms as compared with high depression symptoms have not been described thus far [ 11 , 14 , 21 ]. However, these findings have to be interpreted considering the recent pandemic and the behavioral changes accompanying it [ 52 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, we confirmed the potential discriminative validity of smartphone biomarkers observed among adults in a youth sample [ 51 ]. Although our results on the number of outgoing calls negatively correlating with internalizing symptoms are in line with previous studies in adults [ 13 , 15 , 18 ], differences in mobility patterns of youths with high anxiety symptoms as compared with high depression symptoms have not been described thus far [ 11 , 14 , 21 ]. However, these findings have to be interpreted considering the recent pandemic and the behavioral changes accompanying it [ 52 ].…”
Section: Discussionsupporting
confidence: 91%
“…Study participants with social anxiety and depression were also found to avoid public areas and engage in less leisure activities, choosing instead to spend more time at home after school [ 11 , 12 ]. Studies exploring phone use data have reported the number of outgoing calls and messages to negatively correlate with internalizing symptoms [ 13 , 15 , 18 ]. In addition, ambient light data, an indicator of quality of sleep, were found to be associated with internalizing symptoms [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extant evidence, however, suggests a complex and nuanced relation between smartphone use and mental health, with different types of app use showing different patterns of association. For example, smartphone use behaviors with particular theoretical relevance to stress are calling, mobile messaging, and using social media, but recent work on passively logged data found depression relates negatively to calling [21], whereas it relates positively to social media use [22]. Moreover, research suggests that relations between smartphone app use and mental health differ from person to person [12][13][14][15][16].…”
Section: Smartphone Use Behaviors As Potential Digital Markersmentioning
confidence: 99%
“…More recently, mental health relevant research using personal sensing of raw data streams other than self-report is emerging. This includes methods to sense geolocation [14][15][16], cellular communications [16][17][18][19][20], sleep [20], and physiology [21,22], as examples.…”
Section: Personal Sensingmentioning
confidence: 99%
“…Mental health research and applications with emerging, often more passively sensed, novel data streams like geolocation and cellular communications is still nascent. This research has predominately involved "proof-of-concept" studies that typically include only healthy controls or other convenience samples rather than people with psychiatric disorders [17][18][19]. It has also often used very small sample sizes and/or short monitoring periods [15,17,21,22].…”
Section: Personal Sensingmentioning
confidence: 99%